QUASI-PERIODIC OSCILLATIONS AS GLOBAL HYDRODYNAMIC MODES IN THE BOUNDARY LAYERS OF VISCOUS ACCRETION DISKS - Erkut, M. Hakan; Psaltis, Dimitrios; Alpar, M. Ali (IOP PUBLISHING LTD, TEMPLE CIRCUS, TEMPLE WAY, BRISTOL BS1 6BE, ENGLAND, 2008)
The observational characteristics of quasi-periodic oscillations (QPOs) from accreting neutron stars strongly indicate the oscillatory modes in the innermost regions of accretion disks as a likely source of the QPOs. The inner regions of accretion disks around neutron stars can harbor very high frequency modes related to the radial epicyclic frequency kappa. The degeneracy of kappa with the orbital frequency Omega is removed in a non-Keplerian boundary or transition zone near the magnetopause between the disk and the compact object. We show, by analyzing the global hydrodynamic modes of long wavelength in the boundary layers of viscous accretion disks, that the fastest growing mode frequencies are associated with frequency bands around kappa and kappa +/- Omega. The maximum growth rates are achieved near the radius where the orbital frequency Omega is maximum. The global hydrodynamic parameters such as the surface density profile and the radial drift velocity determine which modes of free oscillations will grow at a given particular radius in the boundary layer. In accordance with the peak separation between kHz QPOs observed in neutron star sources, the difference frequency between two consecutive bands of the fastest growing modes is always related to the spin frequency of the neutron star. This is a natural outcome of the boundary condition imposed by the rotating magnetosphere on the boundary region of the inner disk.
Keywords: accretion; accretion disks; stars: neutron; stars: oscillations; X-rays: stars; x-ray binaries; frequencies; büyüme; toplanma diskleri; yıldız: nötron; yıldız: salınımlar; X-ışınları: yıldız; X-ışın çiftleri; frekansları